Study on vibration characteristic of battery pack of electric excavator under non-stationary random excitation - LI Zhaojun; LI Feibiao; WANG Bo; ZHAO Ming; WU Fangming (Jixie qiangdu)
In practical operation, the loads borne by electric excavators often exhibit significant non-stationary random characteristics, leading to complex vibration phenomena of the battery pack, which directly affects the safe and reliable operation of the battery pack. To address this issue, the characteristics of road excitation, plunger pump pressure pulsation excitation, and impact excitation on electric excavators under complex working conditions were investigated. The vibration transmission paths under various excitations were analyzed, a dynamic model of the battery pack was established, the vibration characteristics of the battery pack under non-stationary random excitation were revealed, and case studies were conducted for analysis and verification. The research shows that reconstructing road excitation signals based on wavelet transform and Grey Wolf Optimization-Variational Mode Decomposition (GWO-VMD) signal analysis algorithm can effectively reflect the characteristics of road excitation. The road excitation borne by electric excavators under driving conditions exhibits significant non-stationary characteristics. Under non-stationary random excitations such as road excitation, the battery pack of electric excavators produces complex and changeable vibrations, whose power spectral density of dynamic response changes significantly with time, showing obvious non-stationary random characteristics.This study provides a reference for the safe and reliable operation of battery packs in electric excavators.